Comparison between SAW and Knowledge based SAW in Recipe Recommendation System - Dewi, Ratih Kartika; Brata , Komang Candra; Afirianto, Tri; Candra , Ersya Nadia (Journal of Information Technology and Computer Science, 2021)
Recipes are used as a reference in processing cooking ingredients to meet personal nutritional needs, considering the ingredients used to make food sold freely that is not necessarily guaranteed in nutritional quality and safe to consume, especially during the pandemic as it is today. So cooking itself becomes a better alternative for the community. With a large number of food recipe options available for various media, the role of a Decision Support System is needed by people who will get food recipe recommendations. Research related to recipe recommendations that have been done are using SAW only and some add experts as a source of knowledge to provide value on the variable time and complexity of cooking recipes. Therefore, in this study, a comparison between the research of recipe recommendations with SAW only and research that added a subsystem of knowledge management derived from experts to support the decision support system of food recipe recommendations was conducted by using correlation testing. The results is there is a strong correlation between knowledge based SAW and user preference to the value of 0.9774. The result is better than SAW only and user preference with the value of 0.7262.